Introduction to philosophy of the human person - Atim, Ben Carlo N. (Makati City : Diwa Learning Systems Inc., 2019)
"This book serves as a material to (a) guide in understanding, reflecting, and analyzing philosophical issues concerning human person, (b) gain knowledge and capacity to doing philosophy, (c) relate and apply philosophical concepts and insights to real life-situations and experiences. and (d) discover meaningful ways on how to live a "flourishing" life".
Includes bibliography.
Keywords: Philosophical anthropology; Human behavior; Philosophy - Textbooks